Inhibition of FAK and VEGFR‐3 binding decreases tumorigenicity in neuroblastoma. Issue 1 (19th July 2013) - Stewart, Jerry E.; Ma, Xiaojie; Megison, Michael; Nabers, Hugh; Cance, William G.; Kurenova, Elena V.; Beierle, Elizabeth A.
Abstract Neuroblastoma is the most common extracranial solid tumor of childhood and is responsible for over 15% of pediatric cancer deaths. Focal adhesion kinase (FAK) is a nonreceptor tyrosine kinase that is important in many facets of tumor development and progression. Vascular endothelial growth factor receptor‐3 (VEGFR‐3), another tyrosine kinase, has also been found to be important in the development of many human tumors including neuroblastoma. Recent reports have found that FAK and VEGFR‐3 interact, and we have previously shown that both of these kinases interact in neuroblastoma. We have hypothesized that interruption of the FAK–VEGFR‐3 interaction would lead to decreased neuroblastoma cell survival. In the current study, we examined the effects of a small molecule, chloropyramine hydrochloride (C4), designed to disrupt the FAK–VEGFR‐3 interaction, upon cellular attachment, migration, and survival in two human neuroblastoma cell lines. We also utilized a murine xenograft model to study the impact of C4 upon tumor growth. In these studies, we showed that disruption of the FAK–VEGFR‐3 interaction led to decreased cellular attachment, migration, and survival in vitro. In addition, treatment of murine xenografts with chloropyramine hydrochloride decreased neuroblastoma xenograft growth. Further, this molecule acted synergistically with standard chemotherapy to further decrease neuroblastoma xenograft growth. The findings from this current study help to further our understanding of the regulation of neuroblastoma tumorigenesis, and may provide novel therapeutic strategies and targets for neuroblastoma and other solid tumors of childhood. © 2013 Wiley Periodicals, Inc.